Linguistic studies and their contributions to the formation of translation theory - Chtaibi, Khalid; Nasirudeen, Abdulwasiu (Faculty of Languages at Al-Madinah International University, 2022)
This research aims to highlight the role of linguistic studies and their contributions to the formation of translation theory during our contemporary history, by studying the stages of translation theory and the most important trends, linguistic and intellectual schools that affected it, as well as to shed light on the position of linguistic studies and the extent of the role it played in formulating translation theory, and if is it possible to rely on one theory in the translation system. The importance of the research lies in the fact that it is one of the scientific studies that address in a specialized and academic manner the subject of linguistic studies and its contributions to the formulation of translation theory, as well as a review of the characteristics, methods and types of translation theories, and their interrelationships with the concept of fidelity in translation. The researcher used the descriptive-analytical approach as the most appropriate in dealing with this research. He concluded that translation gave a lot to the linguistic theory more than the linguistic theory of translation provided, and this is due to the fact that practical translation production has always been a subject of concern and theorizing in linguistic schools more than the dealing of linguistic theory with translation in relation to language.